Multi-cluster flying ad-hoc network for disaster monitoring applications. (25th March 2021) - Joshi, Abhishek; Dhongdi, Sarang C.; Manjarekar, Narayan; Anupama, K.R.
Multiple mini-UAVs can be used in various disaster monitoring applications. These UAVs can be controlled from ground based control stations, or they can form flying ad-hoc networks (FANET) with fully distributed nature of operations. To achieve distributed operations, a set of network protocols need to be developed as a part of protocol stack. Various networking protocols for FANET have been developed in this paper namely clustering, time division based MAC protocol and routing protocol for a particular networking topology. This FANET network can be used for exploring a larger and disjoint terrain with the help of multiple cluster formations. To maintain isolation between clusters and to optimise energy of the network, UAVs make use of adaptive power communication techniques. Extensive simulation experiments have been performed using a platform developed by linking NS-3, ROS and Gazebo tools. Results of network performance are shown with respect to scalability and mobility of UAVs.